Biological soil conditioning and microbial activation in landscape design using bioformulations based on rhizospheric microorganisms - Yakovlieva Anastasia; Voinash Sergey; Orekhovskaya Alexandra; Vanzha Vladimir; Akhtyamova Leisan (BIO Web of Conferences)
In this study, the effectiveness of microbial bioformulations based on rhizospheric microorganisms was evaluated under urban landscaping conditions. The formulations, containing Bacillus subtilis, Trichoderma harzianum, and Azotobacter chroococcum, were applied to sandy loam soils with low organic matter and moderate acidity. The aim was to assess changes in soil microbial abundance, enzymatic activity, physical properties, and plant survival. A 90-day field experiment revealed significant improvements in total microbial count (+71.4%), urease activity (+44.3%), and dehydrogenase activity (+68.6%) in treated plots. Plant survival rate increased by over 34%, while root disease incidence decreased by 65%. Soil bulk density was reduced by 11.6%, and water retention capacity increased by 18.8% in bio-treated soils. These results demonstrate that microbial bioformulations promote biological soil conditioning and enhance plant resilience, providing a sustainable alternative to chemical amendments in landscape design. The findings confirm the ecological and agronomic potential of integrating microbial technologies into urban green infrastructure development.